1995
DOI: 10.1007/bf00400598
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical basis of increased hepatic glucose production in a mouse model of type 2 (non-insulin-dependent) diabetes mellitus

Abstract: SummaryThe mechanism of increased hepatic glucose production in obese non-insulin-dependent diabetic (NIDDM) patients is unknown. The New Zealand Obese (NZO) mouse, a polygenic model of obesity and NIDDM shows increased hepatic glucose production. To determine the mechanism of this phenomenon, we measured gluconeogenesis from U-s4C -glycerol and U-14C-alanine and relevant gluconeogenic enzymes. Gluconeogenesis from glycerol (0.07 + 0.01 vs 0.21 + 0.02 ~tmol 9 min -~ 9 body mass index (BMI) -1, p < 0.005) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 56 publications
5
37
0
Order By: Relevance
“…This has been associated with a NEFA-induced increase in gluconeogenesis [15,16,17,18]. Recently, we have confirmed that the dietary fat-induced increase in gluconeogenesis is associated with increased levels of fructose-1,6-bisphosphatase, a regulatory enzyme in the glucose synthesising pathway [15,19]. Interestingly, it has been suggested that fat-induced hepatic insulin resistance precedes muscle insulin resistance [13] raising the possibility that hepatic insulin resistance can contribute to muscle and fat insulin resistance observed under states of increased dietary fat intake.…”
mentioning
confidence: 63%
“…This has been associated with a NEFA-induced increase in gluconeogenesis [15,16,17,18]. Recently, we have confirmed that the dietary fat-induced increase in gluconeogenesis is associated with increased levels of fructose-1,6-bisphosphatase, a regulatory enzyme in the glucose synthesising pathway [15,19]. Interestingly, it has been suggested that fat-induced hepatic insulin resistance precedes muscle insulin resistance [13] raising the possibility that hepatic insulin resistance can contribute to muscle and fat insulin resistance observed under states of increased dietary fat intake.…”
mentioning
confidence: 63%
“…It was shown in the 1970s that the level of FBPase enzyme activity was double in patients with type 2 diabetes compared with nondiabetics (9), and this increase in FBPase has been confirmed in several animal models of obesity and insulin resistance (2,6,32,33,35,39). Moreover, studies in patients with type 2 diabetes showed increased glycerol gluconeogenesis (27), which was proposed to be caused by an increase in FBPase activity (9).…”
Section: Discussionmentioning
confidence: 95%
“…This was a surprising result, considering the human studies mentioned previously and results from our laboratory and others. These studies showed liver FBPase expression and/or activity to be double that of controls in several models of insulin resistance and obesity including New Zealand obese (NZO) mice (2), db/db mice (6), ob/ob mice (32,33), fa/fa rats (39), and high-fat (HF) fed (HFF) mice and rats (2,35), and in liver biopsies from patients with type 2 diabetes (9).…”
mentioning
confidence: 99%
“…Tritiated H 2 O was then measured by liquid scintillation counting. Glucose oxidation was estimated by assessing the formation of 14 CO 2 from the metabolism of [U- 14 C]glucose (33). The amount of 14 CO 2 was determined by liquid scintillation counting.…”
Section: Elevated Islet Fbpase Impairs Insulin Secretionmentioning
confidence: 99%
“…In addition, FBPase was upregulated fivefold in islets from the diabetes-susceptible obese BTBR mouse compared with the diabetes-resistant C57BL/6 mouse (13). We have previously shown that FBPase is upregulated in the liver of mice or rats fed a high-fat diet (14,15) and in the New Zealand Obese (NZO) mouse, an obese model of type 2 diabetes (14,16). We have recently demonstrated that transgenic mice with specific overexpression of FBPase in the liver displayed increased glycerol gluconeogenesis (17).…”
mentioning
confidence: 93%